Development of a Pharmacodynamic Model of Murine Malaria - Gibbons, Peter Luke (Curtin University, 2015)
The rational design of antimalarial therapies has historically been compromised by a paucity of pharmacodynamic data contributing to resistance through deployment of suboptimal doses. This thesis demonstrates a modified P. berghei murine malaria model for collecting detailed in vivo pharmacodynamic data and novel in silico mathematical model enabling optimisation of dosing and combination therapy. These models contribute to preclinical knowledge and provide the potential to assist in the development of methods to optimise clinical treatment.